MONETARY POLICY AND INSURANCE SECTOR PERFORMANCE IN NIGERIA - Joel Obayagbona; Mayowa Gabriel Ajao (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
ABSTRACT The study empirically examines the effect of monetary policy on the performance of insurance sector in Nigeria for the period 1985 to 2021. The error correction model (ECM) and the cointegration econometric technique were employed for the estimation of the short run and long run relationship. The empirical findings revealed that in the short run, all the hypothesized monetary policy variables (monetary policy rate, cash reserve ratio, reserve requirement, minimum rediscount rate, money supply and interest rate) failed the 5 percent significance level, suggesting that they do not have significant effect on insurance sector performance in Nigeria in the short run. On the other hands, the results of the long run model indicate that monetary policy rate, cash reserve ratio and minimum rediscount rate have significant positive relationship with insurance sector performance. However, those of reserve requirement, money supply and interest rate do not have significant relationship with the performance of insurance sector in Nigeria within the period of investigation. The study recommends among others that since the result from the study has shown that Monetary policy rate significantly impact insurance performance, it therefore follows that activities of insurance firms as well as their overall performance can be adversely impacted by monetary policy decisions if not proactively prepared for and responded to. To this end, management should evolve appropriate strategy that would enable them proactively tackle unfavourable business environment resulting in macroeconomic risks in order to avoid adverse operating losses.